Improvement on Faraday rotation measurement affected by the stray lights on the HL-2A tokamak. (1st September 2022) - Wang, Z H; Li, Y G; Li, Y; Wang, H X; Yi, J; Wen, R N; Shi, Z B
Abstract: Formic-acid (HCOOH, λ = 432.5 μ m) laser P olarimeter- I nterferomet er ( PIer ) has been developed on the HL-2A tokamak, which provides 4 channels of line-integrated electron densities and 4 channels of Faraday rotation angles, respectively. Affected by the stray lights arising from the reflection of the probe waves in the optical system, the measurement of Faraday rotation angles was drastically contaminated during the HL-2A experiments, showing an obvious oscillation modulation during the electron density ramp-up/down. This paper introduces an effective correction approach used to improve the accuracy of Faraday rotation measurement on the HL-2A tokamak. Based on the method, the deviation term originating from the stray lights can be effectively subtracted from the contaminated Faraday rotation measurement. The preliminary result indicates that the interference amplitude on Faraday rotation angle is reduced by about 80%, and the corrected data is consistent with the experimental measurement by using the optical isolator that consists of a λ/4 wave-plate and polarizer under the similar discharges.